Evaluation of Sodium Chloride Concentrations on Growth and Phytochemical Production of Mesembryanthemum crystallinum L. in a Hydroponic System - Giju Eoh; Chulhyun Kim; Jiwon Bae; Jongseok Park (Horticulturae)
Mesembryanthemum crystallinum L., commonly known as the ice plant, is a halophyte recognized for its exceptional salinity tolerance. This study aimed to determine the optimal NaCl concentration for promoting plant growth, D-pinitol, and other phytochemicals in M. crystallinum cultivated in a hydroponics system. Seedlings of M. crystallinum were transplanted into a hydroponic system and subjected to different NaCl concentrations (0, 100, 200, 300, 400, and 500 mM) in the nutrient solution. To evaluate the plant’s response to salinity stress, measurements were conducted on growth parameters, chlorophyll and carotenoid levels, total flavonoid and polyphenol contents, and DPPH scavenging activity. The optimal NaCl concentration for growth was found to be 200 mM, at which the shoot fresh and dry weights were highest. Additionally, total chlorophyll and carotenoid contents were maximized at 200 mM NaCl, with a subsequent decrease at higher concentrations. The highest DPPH scavenging activity was observed in the 200 mM NaCl treatment, which correlated with increased levels of total flavonoids and polyphenols. These results indicated that optimizing NaCl concentration can enhance the antioxidant activity of Mesembryanthemum crystallinum L. The D-pinitol content also peaked at 200 mM NaCl treatment, further supporting its role osmotic adjustment under salinity stress. M. crystallinum exhibited enhanced antioxidant production and cellular protective functions at 200 mM NaCl, which optimized its biochemical defense mechanisms and helped maintain physiological functions under salinity stress. These findings provide valuable insights for agricultural and biological applications, particularly in cultivating M. crystallinum for its bioactive compounds.